Prospective Effect of Pruritus Intensity on the Quality of Life of Neurodermatitis Patients at the NTB Provincial Hospital - Anak Agung Ayu Niti Wedayani; Dedianto Hidajat (Postgraduate, University of Mataram, 2023)
Neurodermatitis is a skin condition that is very itchy and chronic. Its characteristics are characterized by the presence of one or more plaques that experience thickening of the skin. One characteristic of the skin surface of patients with neurodermatitis is tree bark, which is caused by repeated rubbing or scratching responses. The aim of this study was to prospectively determine the effect of pruritus intensity on the quality of life of neurodermatitis patients in Mataram City in August - September 2022. This study was a cross-sectional study to determine the effect of pruritus intensity on the quality of life of neurodermatitis patients in the period August - September 2022. Data on psoriasis patients obtained from the Provincial Hospital of West Nusa Tenggara. Pruritus intensity was measured by VAS and 5D. Quality of life was assessed using the DLQI. There is a significant correlation between the intensity of pruritus and the quality of life of neurodermatitis patients as seen from the value of P=0.000<0.05. Based on the intensity of pruritus, the severity of VAS was obtained in the severe category, namely 36 respondents (50.0%) and 5D in the moderate category, namely 42 respondents (58.3%), and the quality of life was moderately affected by 31 respondents (43.1%). Based on the results of the study, it was found that there was a relationship between the intensity of pruritus and the quality of life of neurodermatitis patients in the city of Mataram. This statement is in accordance with the results of the data that the majority of neurodermatitis patients with moderate-severe pruritus intensity have a quality that has a moderate effect on the patient's life